Acossado, de Godard: diálogos intertextuais - Rodrigues, Diogo Ribeiro (2023)
This research aims to explore the use of intertextuality as a creative asset in the motion picture Breathless, by Jean-Luc Godard, based on a literature focused on critics and history of cinema. The film is often regarded by critics as one of the most emblematic from Nouvelle Vague cinematic movement, and is also praised by its use of citations. These citations are perceived in dialogues with the cinema itself, and also with other media, including television, advertising, paintings, press media, such as newspapers and magazines, and literature. The particular use of language in the picture is also pointed as one of its creative strengths, which makes Breathless a typical model of an intertextual film. The Project is structured including a brief contextualization of Nouvelle Vague, cinematic movement in which Breathless is included. A presentation of intertextuality, based on the concept by Julia Kristeva follows. Then, the film receives a deep analysis, where, based mainly on the works by Michel Marie and Leda Tenório da Motta, the function of intertextuality is highlighted on its thematic and aesthetical construction